Variation of response induced by ceratorhiza on Dendrobium discolor and Phalaenopsis amabilis to odontoglossum ringspot virus infection based on disease intensity and plant resistance level - Mitha valentina treesya Panjaitan; Tundjung Tripeni Handayani; Mahfut Mahfut; Sri Wahyuningsih (UNIVERSITAS NEGERI PADANG, 2022)
The popular cultivated orchid is Phalaenopsis sp. and Dendrobium sp. Mycorrhizae are very important for orchid plants to complete their life cycle. Mycorrhizae are capable of symbiosis with the root system of the host plant which can increase the absorption of these elements. The purpose of this study was to find out the symptoms of infection, the intensity of infectious diseases, the level of resistance to infection. The method used in this study was completely randomized design (CRD) with 2 factors and 4 iterations, the first factor was the type of orchid used Phalaenopsis amabilis (A1) and Dendrobium discolor (A2), and the second factor was the type of administration of mycorrhizal., Virus , and mycorrhizal virus. Observation of the symptoms of the disease is done by looking at the symptoms that appear on the leaves that have been infected with ORSV, while to determine the intensity of the disease and the level of resistance can use a predetermined formula. The results showed that the disease intensity in Phalaenopsis amabilis was more severe than in Dendrobium discolor, which was 40% on each leaf. The level of resistance in Dendrobium discolor is more resistant than Phalaenopsis amabilis, this indicates that Dendrobium discolor on average has a tolerant response. Ceratorhiza could not suppress the intensity of the disease, because from the results obtained, treatment of orchids inoculated with mycorrhiza and virus showed more severe symptoms than treatment only inoculated with virus. Ceratorhiza was unable to increase the resistance of Phalaenopsis amabilis and Dendrobium discolor, this was because treatment of orchids inoculated with mycorrhiza and virus showed a very simple response compared to treatmentonly inoculated with virus.Anggrek populer dibudidayakan adalah Phalaenopsis sp. dan Dendrobium sp. Mikoriza sangat penting bagi tanaman anggrek untuk melengkapi siklus hidupnya. Mikoriza mampu bersimbiosis dengan sistem akar tanaman inang yang dapat meningkatkan daya serap unsur tersebut. Tujuan penelitian untuk mengetahui gejala infeksi, intensitas penyakit menular, tingkat resistensi terhadap infeksi. Metode penelitian: Rancangan Acak Lengkap (RAL) dengan 2 faktor dan 4 iterasi, faktor pertama adalah jenis anggrek yang digunakan Phalaenopsis amabilis (A1) dan Dendrobium discolor (A2), dan faktor kedua adalah jenis pemberian mikoriza, virus, dan virus mikoriza. Pengamatan gejala penyakit dilakukan dengan melihat gejala yang muncul pada daun yang telah terinfeksi ORSV. Hasil penelitian menunjukkan intensitas penyakit pada Phalaenopsis amabilis lebih parah dibandingkan dengan Dendrobium discolor yaitu 40% pada setiap daun. Tingkat ketahanan pada Dendrobium discolor lebih tahan dibandingkan Phalaenopsis amabilis. Dendrobium discolor memiliki respon yang toleran. Ceratorhiza tidak dapat menekan intensitas penyakit. Pengobatan anggrek yang diinokulasi dengan mikoriza dan virus menunjukkan gejala yang lebih parah daripada pengobatan yang hanya diinokulasi virus. Ceratorhiza tidak mampu meningkatkan ketahanan terhadap Phalaenopsis amabilis dan Dendrobium discolor, hal ini dikarenakan perlakuan anggrek yang diinokulasi mikoriza dan virus menunjukkan respon yang sangat sederhana dibandingkan dengan perlakuan yang hanya diinokulasi virus.